Finding balance: using collaboration and evidence to help prevent seniors' falls. (7th October 2012) - Belton, K; Fernandes, J; Sunley, L
Abstract : Background: An estimated one in three persons over the age of 65 is likely to fall at least once a year. In 2008 older adults' falls were the leading cause of injury hospital admissions and injury emergency department visits in Alberta, Canada. From 1999 to 2008 there has been a 30% increase in the number of older adults admitted to hospital due to a fall and a 54% increase in the number of older adults seen in an emergency department due to a fall. Aims/Obejectives/Purpose: The purpose of this initiative was to create greater awareness about seniors' falls and promote targeted, evidence-based falls risk prevention messages. It also aimed to connect seniors, families and health care providers to programmes in their communities. Methods: A communications strategy using various tactics, from social media to print advertisements, was developed to promote proven seniors' falls prevention interventions. Tools and resources were also promoted among practitioners. Results/Outcome: Since 2008 when the initiative started we have seen a 13% increase in seniors reporting they are taking actions to prevent falling. An additional 7% of seniors are 'keeping active' and a further 9% are 'watching their step, ' two key messages of the strategy. Significance/Contribution to the Field: Falls prevention among seniors is pivotal to reducing the burden of injury on Albertans. Providing knowledge, tools and support to community stakeholders within a variety of disciplines is a viable method to address falls among seniors, perhaps influencing practice in other injury areas.